Ordinances, ch. 1, tit. 1, § 3, THE BOTTINEAU PIONEER, Dec. 13, 1888, at 4 (Bottineau, North Dakota) - (:unkn) unknown (My University, 1888)
Any person found armed within the corporate limits of the village of Bottineau with a dirk, dagger, sword, pistol or pistols, or other offensive or dangerous weapons, without reasonable cause to fear an assault or other injury or violence to his person or to his family or property, shall, upon conviction before said justice, be punished by a fine not exceeding ten dollars, or by imprisonment in the village jail not exceeding term of thirty days.
Keywords: CARRY